Case volume and rate are associated with outcomes in geriatric trauma: A case for geriatric trauma centers?. Issue 2 (18th February 2023) - Kojima, Mitsuaki; Endo, Akira; Zakhary, Bishoy; Shoko, Tomohisa; Firek, Matthew; Coimbra, Raul
Abstract : This study showed the association between geriatric trauma case volume and geriatric case rate with outcomes of elderly patients with severe injury. Mortality and complication rates were lower in centers that treat higher volumes and rates of geriatric trauma patients. Abstract : BACKGROUND: Increased morbidity and mortality in geriatric trauma patients are usually due to decreased physiologic reserve and increased comorbidities. It is unclear whether geriatric trauma case volume and rates correlate with survival. We hypothesized that geriatric patients would have increased survival when treated in high-case volume and rate trauma centers. METHODS: A retrospective cohort study was conducted using the Trauma Quality Improvement Program database between 2015 and 2019. Geriatric trauma patients (≥65 years) with severe injury (Injury Severity Score ≥16) were included. Geriatric case volume (GCV) was defined as the mean annual number of treated geriatric trauma patients, while geriatric case rate (GCR) was the mean annual number of elderly trauma patients divided by all trauma patients in each center. Trauma centers were classified into low-, medium-, and high-volume and rate facilities based on GCV and GCR. The association of GCV and GCR with in-hospital mortality and complication rates was assessed using the generalized additive model (GAM) and multivariate generalized linear mixed model adjusted for patient characteristics (age, sex, Injury Severity Score, Revised Trauma Score, and Modified Frailty Index) as fixed-effect variables and hospital characteristics as random effect variables. RESULTS: A total of 164, 818 geriatric trauma patients from 812 hospitals were included in the analysis. The GAM plots showed that the adjusted odds of in-hospital mortality decreased as GCV and the GCR increased. The generalized linear mixed model revealed that both high GCV and high GCR hospitals had lower mortality rates than low GCV and GCR hospitals (adjusted odds ratio [95% confidence interval], high GCV and high GCR centers; 0.82 [0.72–0.92] and 0.81 [0.73–0.90], respectively). CONCLUSION: Both high geriatric trauma volume and rates were associated with decreased mortality of geriatric trauma patients. Consolidation of care for elderly patients with severe injury in specialized high-volume centers may be considered. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :